Dual-functional thermal management materials for highly thermal conduction and effectively heat generation. (1st August 2022) - Wang, Zhi-Guo; Jin, Yi-Fei; Hong, Rui; Du, Jiguang; Dai, Kun; Zhang, Guo-Qiang; Gao, Jiefeng; Xu, Ling; Xu, Jia-Zhuang; Li, Zhong-Ming
Abstract: Overheating and overcooling operation temperatures are both detrimental to the reliability of electronic devices. However, it is challenging to synchronously achieve effective heat dissipation and rapid heat generation. Herein, dual-function thermal management materials were prepared by constructing bilateral conductive networks. Favorable pathways for heat conduction were paved by directional arrangement of boron nitride nanosheets (BNNSs) and aramid nanofibers (ANFs). The interconnected silver nanowire (AgNW) network with abundant cross-bar junctions was assembled onto the upper surface of the BNNS/ANF layer, establishing the structural basis for electrical heating. The 30 wt% BNNS/ANF@AgNW film exhibited the excellent in-plane TC of 31.3 W/mK and Joule heat performance. The mechanical strength of dual-function composite films with remarkable flexibility was beyond 100 MPa. Our work paves the valuable way for developing multifunctional thermal management materials. Highlights: Dual-functional thermal management materials were prepared by constructing bilateral conductive networks. Superior and highly anisotropic thermal conductivity was achieved by directional arrangement of boron nitride nanosheets. Favorable Joule heat performance was obtained by assembling dense and interconnected silver nanowire network.